Genetic determinants of warfarin dosing in the Han-Chinese population. (December 2009) - Lee, MT Michael; Chen, Chien-Hsiun; Chou, Ching-Heng; Lu, Liang-Suei; Chuang, Hui-Ping; Chen, Ying-Ting; Saleem, Amir N; Wen, Ming-Shien; Chen, Jin-Jer; Wu, Jer-Yuarn; Chen, Yuan-Tsong
Warfarin, a widely prescribed oral anticoagulant, is used for the prevention of thromboembolism. Polymorphisms in CYP2C9 and VKORC1 have been shown to be associated with warfarin dose requirements. However, it is likely that other genes could also affect warfarin dose.Aims: In this study, we aimed to identify additional genes influencing warfarin dosing in the Han-Chinese population.Materials & methods: In this study, we screened for SNPs in 13 genes ( VKORC1, CYP2C9, CYP2C18, PROC, APOE, EPHX1, CALU, GGCX, ORM1, ORM2, factor II, factor VII and CYP4F2 ) and tested their associations with warfarin dosing with univariate and multiple regression analysis.Results: Polymorphisms in the VKORC1 gene have the strongest effects on warfarin dose, followed by CYP2C9*3 . In addition, our results showed that CYP2C18, PROC and EPHX1 have small but significant associations with warfarin dose. In multiple regression analysis, PROC and EPHX1 explained 3% of the dose variation. The incorporation of these two genes into warfarin dosing algorithms could improve the accuracy of prediction in the Han-Chinese population.